A new modular procedure for industrial plant simulations and its reliable implementation. (1st January 2016) - Carcasci, C.; Marini, L.; Morini, B.; Porcelli, M.
Abstract: Modeling of industrial plants, and especially energy systems, has become increasingly important in industrial engineering and the need for accurate information on their behavior has grown along with the complexity of the industrial processes. Consequently, accurate and flexible simulation tools became essential yielding the development of modular codes. The aim of this work is to propose a new modular mathematical modeling for industrial plant simulation and its reliable numerical implementation. Regardless of their layout, a large class of plant's configurations is modeled by a library of elementary parts; then the physical properties, compositions of the working fluid, and plant's performance are estimated. Each plant component is represented by equations modeling fundamental mechanical and thermodynamic laws and giving rise to a system of algebraic nonlinear equations; remarkably, suitable restrictions on the variables of such nonlinear equations are imposed to guarantee solutions of physical meaning. The proposed numerical procedure combines an outer iterative process which refines plants characteristic parameters and an inner one which solves the arising nonlinear systems and consists of a trust-region solver for bound-constrained nonlinear equalities. The new procedure has been validated performing simulations against an existing modular tool on two compression train arrangements with both series and parallel-mounted compressors. Highlights: A numerical modular tool for industrial plants simulation is presented. Mathematical modeling is thoroughly described. Solution of the nonlinear system is performed by a trust-region Gauss–Newton solver. A detailed explanation of the optimization solver named TRESNEI is provided. Code flexibility and robustness are investigated through numerical simulations.